A longitudinal, within‐person investigation of the association between the P3 ERP component and externalizing behavior problems in young children. (25th September 2018) - Petersen, Isaac T.; Hoyniak, Caroline P.; Bates, John E.; Staples, Angela D.; Molfese, Dennis L.
Abstract : Background: Externalizing problems, including aggression and conduct problems, are thought to involve impaired attentional capacities. Previous research suggests that the P3 event‐related potential (ERP) component is an index of attentional processing, and diminished P3 amplitudes to infrequent stimuli have been shown to be associated with externalizing problems and attention‐deficit/hyperactivity disorder (ADHD). However, the vast majority of this prior work has been cross‐sectional and has not examined young children. The present study is the first investigation of whether within ‐individual changes in P3 amplitude predict changes in externalizing problems, providing a stronger test of developmental process. Method: Participants included a community sample of children ( N  =   153) followed longitudinally at 30, 36, and 42 months of age. Children completed an oddball task while ERP data were recorded. Parents rated their children's aggression and ADHD symptoms. Results: Children's within‐individual changes in the P3 amplitude predicted concomitant within‐child changes in their aggression such that smaller P3 amplitudes (relative to a child's own mean) were associated with more aggression symptoms. However, changes in P3 amplitudes were not significantly associated with ADHD symptoms. Conclusions: Findings suggest that the P3 may play a role in development of aggression, but do not support the notion that the P3 plays a role in development of early ADHD symptoms.